3-Chloropropane-1,2-diol (3-MCPD) in soy sauce: A review on the formation, reduction, and detection of this potential carcinogen - Bai, Q.L.; Khor, S.M. (2015)
Soy sauce, a dark-colored seasoning, is added to enhance the sensory properties of foods. Soy sauce can be consumed as a condiment or added during the preparation of food. There are 3 types of soy sauce: fermented, acid-hydrolyzed vegetable protein (acid- HVP), and mixtures of these. 3-Chloropropane-1,2-diol (3-MCPD) is a heat- produced contaminants formed during the preparation of soy sauce and was found to be a by-product of acid-HVPproduced soy sauce in 1978. 3-MCPD has been reported to be carcinogenic, nephrotoxic, and reproductively toxic in laboratory animal testing and has been registered as a chemosterilant for rodent control. 3-MCPD is classiﬁed as a possible carcinogenic compound, and the maximum tolerated limit in food has been established at both national and international levels. The purpose of this review is to provide an overview on the detection of 3-MCPD in soy sauce, its toxic effects, and the potential methods to reduce its concentration, especially during the production of acid-HVP soy sauce. The methods of quantiﬁcation are also critically reviewed with a focus on efﬁciency, suitability, and challenges encountered in analysis.